Academic stress in accounting students: an empirical study - Zhenghong, J. Hou; Shinde, Jaysinha S.; Willems, John (FEP, 2013)
The purpose of the current study is to develop and validate an instrument for measuring academic stress in accounting students. Extant research indicates that academic stress has an adverse impact on the quality of student life and academic success. Academic stressors are categorized and examined to explore the relationship between the stressors and academic stress. Data collected from 59 accounting students in a Midwestern university in the United States are analyzed using various statistical methods, including factor analysis and scree plots, to examine the dimensionality of the concept of academic stress. A scale for measuring academic stress is developed and psychometrically tested. The validity and reliability of the instrument are also tested. The factor analysis of the instrument yields five underlying factors relating to academic stress. Statistical testing indicates that the instrument is a reliable and valid measurement of academic stress in accounting students. The validated instrument is subsequently administered to 98 accounting undergraduate students. The results of the present study indicate that differences in stress scores are based upon gender and educational level.